2022
DOI: 10.3389/fpsyg.2021.684723
|View full text |Cite
|
Sign up to set email alerts
|

Pseudomentalization as a Challenge for Therapists of Group Psychotherapy With Drug Addicted Patients

Abstract: One of the main challenges in group therapy with drug-addicted patients is collective pseudomentalization, i.e., a group discourse consisting of words and clichés that are decoupled from any inner emotional life and are poorly related to external reality. In this study, we aimed to explore the phenomenology of pseudomentalization and how it was addressed by the therapist in an outpatient group for drug-addicted patients. The group was composed of seven members, and the transcripts of eight audio-recorded sessi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Inderhaug & Karterud ( 2015 ) has written well about pseudomentalizing in groups, they suggested that therapist failed to manage authority and overplayed the not-knowing position as an explanation for chaotic group sessions. Esposito and colleagues ( 2021 ) have made an important contribution to the understanding of pseudomentalizing in groups with substance addicted patients, where they suggest that there are three types of pseudomentalizing where the intrusive type is perhaps what is most recognizable in our study. The intrusive pseudomentalizing appears certain about mental states and lacks any connection between thoughts and feelings (Esposito et al ., 2021 ).…”
Section: Discussionmentioning
confidence: 60%
See 3 more Smart Citations
“…Inderhaug & Karterud ( 2015 ) has written well about pseudomentalizing in groups, they suggested that therapist failed to manage authority and overplayed the not-knowing position as an explanation for chaotic group sessions. Esposito and colleagues ( 2021 ) have made an important contribution to the understanding of pseudomentalizing in groups with substance addicted patients, where they suggest that there are three types of pseudomentalizing where the intrusive type is perhaps what is most recognizable in our study. The intrusive pseudomentalizing appears certain about mental states and lacks any connection between thoughts and feelings (Esposito et al ., 2021 ).…”
Section: Discussionmentioning
confidence: 60%
“…Is a high tempo and the party like quality of the dialogue an example of pseudomentalizing, the antisocial version? Pseudomentalizing has been described as potentially very destructive in group therapy (Esposito et al ., 2021 ). Therapists often have problems with discovering when pseudomentalizing is present, they lack authority to steer the group away from pseudomentalizing and furthermore, we assume that a pseudomentalistic dialogue does not have the potential to produce change.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, this is of fundamental importance in the study of integrity. It is possible, in fact, that more informative results emerge from studies that focus on the reciprocity of variables (Webb et al, 2010), since adherence and competence could show a greater impact on the outcome precisely in the interaction with other aspects of the process and with the characteristics of patients and therapists themselves (Esposito et al, 2021(Esposito et al, , 2022. In the current review, only three In this regard, it is important that researchers report in their studies not only effect sizes of the treatment but also effect sizes of the relationship between treatment integrity and outcome.…”
Section: Discussionmentioning
confidence: 99%